Study of the Structural, Magnetic and Transport properties of La3+ Doped Cu-Zn Ferrite - Nahar, K.; Hossain, M. A.; Roy, P.; Khan, M. N. I.; Sikder, S. S. (Journal of Scientific Research, 2020)
Crystalline La doped Cu-Zn ferrite with compositions Cu0.15Zn0.85LaxFe2-xO4 [ x = 0.00, 0.02, 0.04, 0.06 and 0.08] were synthesized by using conventional solid state reaction method technique. X-ray diffraction pattern (XRD), Crystalline La doped Cu-Zn ferrite with compositions Cu0.15Zn0.85LaxFe2-xO4 [x = 0.00, 0.02, 0.04, 0.06 and 0.08] were synthesized by using conventional solid state reaction method technique. X-ray diffraction pattern (XRD), scanning electron micrographs (SEM), hysteresis loop (M-H) curves and frequency dependent resistivity were employed to inspect the effect of La3+ doping on the structure, microstructure, magnetic and transport properties of the specimens. All the specimens exhibited fcc type cubic spinel structure where the particle size were within 500-1600 nm range. Magnetically ferromagnetic phenomenon was found for all the samples where the effect of La3+ doping consequence on the variation of various parameters like saturation magnetization (Ms), coercivity (Hc) and remanent magnetization (Mr). The resistivity tuned by frequency for all the samples presented the decreasing phenomenon with the increase of applied frequency.